Lithuanian laborers in Nazi-occupied Austria 1942–1945 - Bubnys, Arūnas (Genocidas ir rezistencija, 2020)
The theme of forced and voluntary labor of Lithuanians in Nazi Germany has been nearly forgotten and not studied by Lithuanian historians in recent decades. Even less examined has been the forced labor and imprisonment of Lithuanians in Nazi-annexed Austria. Up to 70,000 Lithuanians could have been deported to Germany during World War II. This is a fairly significant part of the Lithuanian population, which has affected Lithuanian Poles, Roma and minority Lithuanians most severely. When assessing the types and scale of Nazi violence, apart from the genocide of the Jews, the conclusion is that it affected people in Lithuania most who suffered from forced labor and forced removal from residential areas. At the current stage of research, we can predict that at least a thousand Lithuanians, forcibly or voluntarily, ended up in Nazi-annexed Austria during World War II. The national composition was made up predominantly of Lithuanians, Poles and Russians. Lithuanians were transported to Austria en masse from 1942 to almost until the defeat of Nazi Germany in the Second World War. The vast majority of Lithuanians brought to Austria worked in industrial and transport companies. The overview of the workplaces shows that the majority of the Lithuanians was concentrated in Vienna, Kapfenberg and Marktle. A smaller number of Lithuanians were employed by farmers in the villages.Part of the Lithuanian population came to Austria as political prisoners or for racial reasons (Jews). Another part was imprisoned while staying in Austria for disciplinary violations or attempts to flee to Lithuania. The imprisoned residents of Lithuania were mainly held in the Mauthauzen concentration camp and its branches (Guzen, etc.). At the current stage of research, it can be predicted that at least one hundred inhabitants of Lithuania of different nationalities were imprisoned in the Mauthauzen concentration camp. The revised List of 68 Lithuanians who died in Mauthauzen concentration camp (some persons may be Latvian residents) listed below in appendix 1 (list clarified by LGGRTC employee Stanislovas Buchaveckas).
Keywords: german occupation; Austria; repressions; forced labor